Knowledge acquisition via internet-enabled platforms: Examining incrementally and non-incrementally internationalizing SMEs. Issue 1 (11th February 2019) - Glavas, Charmaine; Mathews, Shane; Russell-Bennett, Rebekah
Abstract : Purpose: Technology has profoundly transformed the international business environment, particularly regarding the flow of information and the way in which knowledge is acquired and shared. Yet, the extent of this transformation is still underappreciated. The purpose of this paper is to examine how small and medium-sized enterprise (SME) owner/founders acquire and utilize knowledge for internationalization via internet-enabled platforms. Design/methodology/approach: The empirical analysis draws on multiple case study methodology to examine 13 Australian SME owner/founders and the knowledge they acquire from utilization of internet-enabled platforms. Findings: The analysis reveals four differing types of internet-enabled experiences: "technical internet-enabled experiences, " "operational internet-enabled experiences, " "functional internet-enabled experiences, " and "immersive internet-enabled experiences." The findings indicate that internet-enabled experiences can generate both explicit and tacit forms of knowledge for the pre, early and later phases of internationalization. Practical implications: The findings provide a structured approach by allowing SMEs to "plot" themselves against the classification of internet-enabled experiences to denote their level of technological involvement, and for discerning the types of knowledge that can be acquired. The findings are particularly helpful for owner/founders, highlighting that internet-enabled platforms are affecting the ways in which knowledge can be acquired and applied to international businesses processes. Originality/value: The findings extend the conventional notion of knowledge acquisition for international business by highlighting how information and knowledge can be acquired via internet-enabled platforms. The findings lay the necessary groundwork for building an evidence base and theoretically extending the concept of knowledge acquisition via internet-enabled platforms.